Epidermal Growth Factor Receptor Mutations as a Prognostic Factor in Korean Patients with Advanced Lung Adenocarcinoma Who Had Not Been Treated with Received Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors - Kim, Seung Tae; Choi, Yoon Ji; Park, Kyong Hwa; Oh, Sang Cheul; Seo, Jae Hong; Shin, Sang Won; Kim, Jun Suk; Kim, Yeul Hong (Chemotherapy (Basel), 2011)
Background: Epidermal growth factor receptor (EGFR) mutations as prognostic marker in patients with non-small cell lung cancers remain controversial. In particular, there is only a limited amount of data on the subject in Asian patients with advanced lung adenocarcinomas. Patients and Methods: We analyzed 50 patients with advanced lung adenocarcinoma, who received best supportive care with and without cytotoxic chemotherapy, between March 2006 and December 2008. The patients had never been treated with EGFR tyrosine kinase inhibitors. Tumor tissues of all 50 patients were analyzed for the status of EGFR gene mutations. Results: The median age of patients was 64 years (range 32–84) at diagnosis, and the male/female ratio was 2.6/1.0. Thirty-two patients were current or ever smokers. EGFR gene mutations were detected in 11 patients (22%). Seven of them had in-frame deletion within exon 19, resulting in the loss of codon 746 through 750 (delE746-A750), 2 patients had L858R in exon 21, and 2 patients had point mutation at codon 709 in exon 18, resulting in the substitution of glycine either with glutamic acid or alanine. The status of EGFR mutations was not significantly associated with gender, smoking status, ages, metastatic sites and number of metastasized sites. Seventeen patients received best supportive care without cytotoxic chemotherapy and 33 patients received the standard platinum-based doublet chemotherapy. The median overall survival was 8.90 months (95% CI 4.01–13.79). There were no significant differences in overall survival (p = 0.282) according to the status of EGFR mutations. Conclusion: These results suggest that EGFR mutation is not a prognostic marker in Korean patients with advanced lung adenocarcinoma who had not been treated with EGFR tyrosine kinase inhibitors.